Fauna and abundance of ticks of the superfamily Ixodoidea in Central Tajikistan - E. H. Iskandarov; M. R. Sahimov (Российский паразитологический журнал, 2024)
The purpose of the research is to determine the species composition and abundance of ixodid and argasid ticks in Central Tajikistan.Materials and methods. The work was carried out during 2017–2022 at the Institute of Biological Safety and Biotechnology Problems of the Tajik Academy of Agricultural Sciences and livestock farms in Central Tajikistan. Ticks were collected mainly from cattle, sheep, goats, horses, donkeys, dogs, cats and wild animals. In addition, livestock yards, walking areas, parking areas and daytime rest areas of animals were examined for tick infeсtion.Results and discussion. During the study period, 3,348 domestic and 183 wild animals were examined. A total of 6,810 tick specimens were collected, which belong to 15 species of the superfamily Ixodoidea: Rhipicephalus turanicus B. Pom., 1940, Rh. bursa Can. et Franz., 1877, Hyalomma anatolicum Koch, 1844, H. asiaticum P. Sch. et E. Schl., 1929, H. detritum P. Sch., 1919, H. plumbeum Panz., 1795 (H. marginatum Koch, 1844), H. scupense P. Sch., 1918, H. dromedarii Koch, 1844, H. aegyptum L., 1758, Haemaphysalis punctata Can. et Fanz, 1877, Haem. sulcata Can. et Fanz, 1877, Dermacentor marginatus Sulz., 1776, D. pictus Herm., 1804 (D. reticulatus Fabricius, 1794), Ixodes redikorzevi B. Pom., 1950, Alveonasus lahorensis Neum., 1908 (Ornithodoros lahorensis Neumann, 1908, A. canestrinii Canestrini, 1890). The predominant tick species are H. anatolicum – 2563 specimens (37.6%), H. detritum – 1739 specimens (25.5%) and H. asiaticum – 1496 specimens (22.0%). These tick species are of great epizootological and epidemiological significance. They are carriers of many protozoan and infectious diseases of animals and humans. In smaller quantities, ticks Hyalomma plumbeum (H. marginatum), H. scupense, H. dromedarii, H. aegyptum, Haemaphysalis punctata, Haem. sulcata, Rhipicephalus bursa, Dermacentor рictus (D. reticulatus), D. marginatus were found. Their numbers range from 0.3 to 1.3%.